Competitive interactions between a nonmycorrhizal invasive plant, Alliaria petiolata, and a suite of mycorrhizal grassland, old field, and forest species - Gary T. Poon; Hafiz Maherali (PeerJ, 2015)
The widespread invasion of the nonmycorrhizal biennial plant, Alliaria petiolata in North America is hypothesized to be facilitated by the production of novel biochemical weapons that suppress the growth of mycorrhizal fungi. As a result, A. petiolata is expected to be a strong competitor against plant species that rely on mycorrhizal fungi for nutrient uptake services. If A. petiolata is also a strong competitor for soil resources, it should deplete nutrients to levels lower than can be tolerated by weaker competitors. Because the negative effect of losing the fungal symbiont for mycorrhizal plants is greatest when nutrients are low, the ability of A. petiolata to simultaneously suppress fungi and efficiently take up soil nutrients should further strengthen its competitive ability against mycorrhizal plants. To test this hypothesis, we grew 27 mycorrhizal tree, forb and grass species that are representative of invaded habitats in the absence or presence of competition with A. petiolata in soils that had previously been experimentally planted with the invader or left as a control. A history of A. petiolata in soil reduced plant available forms of nitrogen by >50% and phosphorus by 17% relative to control soil. Average mycorrhizal colonization of competitor species was reduced by >50% in A. petiolata history versus control soil. Contrary to expectations, competition between A. petiolata and other species was stronger in control than history soil. The invader suppressed the biomass of 70% of competitor species in control soil but only 26% of species in history soil. In addition, A. petiolata biomass was reduced by 56% in history versus control soil, whereas the average biomass of competitor species was reduced by 15%. Thus, our results suggest that the negative effect of nutrient depletion on A. petiolata was stronger than the negative effect of suppressing mycorrhizal colonization on competitor species. These findings indicate that the inhibitory potential of A. petiolata on competitor species via mycorrhizal suppression is not enhanced under nutrient limitation.